The Microbiome of Posidonia oceanica Seagrass Leaves Can Be Dominated by Planctomycetes - Kohn, Timo; Rast, Patrick; Kallscheuer, Nicolai; Wiegand, Sandra; Boedeker, Christian; Jetten, Mike S. M.; Jeske, Olga; Vollmers, John; Kaster, Anne-Kristin; Rohde, Manfred; Jogler, Mareike; Jogler, Christian (Frontiers in Microbiology, 2020)
Seagrass meadows are ubiquitous, fragile and endangered marine habitats, which serve as fish breeding grounds, stabilize ocean floor substrates, retain nutrients and serve as important carbon sinks, counteracting climate change. In the Mediterranean Sea, seagrass meadows are mostly formed by the slow-growing endemic plant Posidonia oceanica (Neptune grass), which is endangered by global warming and recreational motorboating. Despite its importance, surprisingly little is known about the leaf surface microbiome of P. oceanica. Using amplicon sequencing, we here show that species belonging to the phylum Planctomycetes can dominate the biofilms of young and aged P. oceanica leaves. Application of selective cultivation techniques allowed for the isolation of two novel planctomycetal strains belonging to two yet uncharacterized genera.